Projecting the Future Ageing Population in Post-2045: The Today’s Millenials Perspectives - Zaky Mas’ul (Jurnal Jamsostek, 2023)
Indonesian elderly population in 2045 is projected to be 275% compared to 2015, in which elderly population are embedded with vulnerability and dependence as natural traits. Meanwhile, most of the elderly post-2045, millennials as the primary candidate, are predictedto have better capabilities than the nowadays elderly. Most literature, including lesson learnedfrom countries that experience ageing population, mainly discusses ageing from past or present phenomena. There are still missing links in considering the younger generation as the primary candidates for the ageing population in the future. Thus, how does millennials’ competitivenessas the primary candidate generation of the ageing population post-2045, and how far is the feasibility of social security for the elderly population, particularly regarding system and reliability. This research uses explanatory sequential mixed methods, in which quantitative attains initial results and then qualitative stage builds on these results. This study follows the framework of sociology of the future and sociology of generation. The challenge in 2045 is not about the demographic shift, but it presents the complexityof a new society in future. Considering the competitiveness of millennials, Indonesia may experience the second phase of the demographic bonus since the elderly post-2045 can contribute economically. Meanwhile, most current social assistance for the elderly is unreliableregarding the targeting and distribution system. Besides, the rapid growth of an ageing population is disproportionate to the slow growth of beneficiary coverage and pension contribution schemes. Some practical ways can be introduced and implemented in the short term, particularly regarding some  issues:  retirement  age,  dependency  ratio  framework,  job  field for  elderly,  the  digital productivity, non-state welfare provision, and pension funds for informalworkers.